The spell of the sorcerer's skull - Bellairs, John (Puffin Books, 2004)
When Johnny Dixon takes a tiny skull from a haunted dollhouse, demonic forces are released, capturing Professor Childermass and leading Johnny on a harrowing chase to a deserted island off the coast of Maine.